2022
DOI: 10.3390/educsci12100685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Socio-Economic Consequences of Distance Learning during the COVID-19 Pandemic

Abstract: The research analysis shows that children in mainstream schools suffered from psychological deterioration (aggressive behaviour, depressive moods, despair about academic underachievement, etc.) when governments implemented measures to manage the COVID-19 pandemic, and children’s education took place remotely for a significant period. This was caused by the lack of social contact, which in turn contributed to the lack of knowledge in individual subjects, a deterioration in physical condition (spinal problems, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Gao et al reported that family support had a strong correlation with e-learners’ engagement ( r = 0.475, p < 0.001) [ 26 ]. Research into the issue of COVID-19 distance learning in different countries has identified socioeconomic context as an influencing factor on the students’ distance learning and learning achievements [ 27 ]. Research indicates that, in general, lower family socioeconomic characteristics may work against higher education adjustments [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al reported that family support had a strong correlation with e-learners’ engagement ( r = 0.475, p < 0.001) [ 26 ]. Research into the issue of COVID-19 distance learning in different countries has identified socioeconomic context as an influencing factor on the students’ distance learning and learning achievements [ 27 ]. Research indicates that, in general, lower family socioeconomic characteristics may work against higher education adjustments [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are less likely to be entitled to privileges such as receiving an internet allowance to cover the costs of paying for high-speed internet and receiving suitable devices to conduct online classes. Further, continued administrative assistance might have been limited due to budget cuts on salaries, material costs for equipment, teaching/learning services, and technology training (Gaidelys et al, 2022). Because younger faculty members are not prioritized in receiving such support, it becomes more challenging for them to cope with the demands of their workload.…”
Section: Mental Health-associated Risk Factors At This Time Of the Pa...mentioning
confidence: 99%
“…The study conducted by Gaidelys et al [25] revealed the following positive aspects of distance education: when studying at home, students feel more comfortable, they can get the necessary help, record lessons, and review them later, and select a quiet and comfortable environment for studying. The authors also note that a safe home environment created the preconditions for students to feel psychologically calmer and safer.…”
Section: The Positive Effects Of Distance Educationmentioning
confidence: 99%
“…Gaidelys et al [25] identified the following factors which affected distance education: IT and infrastructure; teaching/learning and assessment; assistance to teachers and students; educational content; cooperation; physical and mental health; involvement of students; digital competences; study environment; and organisation.…”
Section: Assessment Of the Effects Of Distance Educationmentioning
confidence: 99%